Analisis Filosofis Pentingnya Pelatihan Penginjilan Untuk Menumbuhkan Minat Menginjil Anggota Jemaat Gereja Masehi Advent Hari Ketujuh Berdasarkan 2 Timutius 4:5 - Misdon Silalahi; R.W. Sagala; Alvyn Hendriks (Peneliti.net, 2022)
The purpose of this research is to find out how important evangelism training is for congregation members so that the congregation has an understanding of what evangelism is. The method used in this article is a library method with a descriptive approach. The results of the study indicate that the role of the pastor or servant of God is not enough just to prepare sermons, pray and worship, but there must be things done outside of that in growing and motivating the congregation to worship. Training for church members has many benefits. Church members will increase in terms of knowledge, abilities and skills, which will have positive implications for the growth of the congregation spiritually and in terms of the number of members.